2016
DOI: 10.1002/srin.201600218
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Evolution of Non-Metallic Inclusions during Deoxidation by Al Addition in BOF Crude Steel

Abstract: In order to know the types of inclusions in BOF crude steel and their evolution during Al deoxidation, steel samples are taken from industry and deoxidation with aluminum experiments are carried out in laboratory. The results show that the BOF crude steel is an important source of inclusions. A lot of (Fe, Mn)O inclusions and some BOF slag droplets (mainly calcium silicates) were found in BOF crude steel. During Al deoxidation, alumina clusters could be formed because of homogeneous nucleation, while some sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…(5)). Similar results are also reported in an earlier study 30) by the present authors. Therefore, the main type of inclusions are alumina inclusions before LF refining (Type 1 and Type 2) as given in Table 4 and Fig.…”
Section: Evolution Of Inclusions In Medium Mn Steelsupporting
confidence: 93%
“…(5)). Similar results are also reported in an earlier study 30) by the present authors. Therefore, the main type of inclusions are alumina inclusions before LF refining (Type 1 and Type 2) as given in Table 4 and Fig.…”
Section: Evolution Of Inclusions In Medium Mn Steelsupporting
confidence: 93%
“…5. At the same time, Chi et al 56) investigated the inclusions in crude steel of BOF converter, and also found some MgO islands in calcium silicate inclusions. According to their study, these MgO islands transformed into MgO•Al 2 O 3 spinel islands in calcium aluminates during deoxidation by Al.…”
Section: Formation Of Spinel Inclusions From Mgomentioning
confidence: 96%
“…inclusions. [43][44][45][46][47] Although [Al] partially and even completely replaces [Ca] and [Mg] in Al-Ca-Mg-O composite inclusion with the aluminum concentration increasing in steel liquid, [Ca] and [Mg] could enter steel liquid from slag, which may inhibit the formation of high-hardness Al 2 O 3 inclusion in steel liquid. [48] The sulfur content in the steel liquid first increases, which may promote the formation of Al-Mg-O-wrapped Mn(Ca)S and the precipitation of MnS inclusions in the steel.…”
Section: Mechanism Of Inclusion Evolution For Different Aluminum Conc...mentioning
confidence: 99%